The impact of a digital joint school educational programme on post-operative outcomes following lower limb arthroplasty: a retrospective comparative cohort study - Joanne Gray; Stephen McCarthy; Esther Carr; Gerard Danjoux; Rhiannon Hackett; Andrew McCarthy; Peter McMeekin; Natalie Clark; Paul Baker (BMC, 2022)
Abstract Background As part of an ongoing service improvement project, a digital 'joint school' (DJS) was developed to provide education and support to patients undergoing total hip (THR) and total knee (TKR) replacement surgery. The DJS allowed patients to access personalised care plans and educational resources using web-enabled devices, from being listed for surgery until 12 months post-operation. The aim of this study was to compare a cohort of patients enrolled into the DJS with a cohort of patients from the same NHS trust who received a standard 'non-digital' package of education and support in terms of Health-Related Quality of Life (HRQoL), functional outcomes and hospital length of stay (LoS). Methods A retrospective comparative cohort study of all patients undergoing primary TKR/THR at a single NHS trust between 1st Jan 2018 and 31st Dec 2019 (n = 2406) was undertaken. The DJS was offered to all patients attending the clinics of early adopting surgeons and the remaining surgeons offered their patient's standard written and verbal information. This allowed comparison between patients that received the DJS (n = 595) and those that received standard care (n = 1811). For each patient, demographic data, LoS and patient reported outcome measures (EQ-5D-3L, Oxford hip/knee scores (OKS/OHS)) were obtained. Polynomial regressions, adjusting for age, sex, Charlson Comorbidity Index (CCI) and pre-operative OKS/OHS or EQ-5D, were used to compare the outcomes for patients receiving DJS and those receiving standard care. Findings Patients that used the DJS had greater improvements in their EQ-5D, and OKS/OHS compared to patients receiving standard care for both TKR and THR (EQ-5D difference: TKR coefficient estimate (est) = 0.070 (95%CI 0.004 to 0.135); THR est = 0.114 (95%CI 0.061 to 0.166)) and OKS/OHS difference: TKR est = 5.016 (95%CI 2.211 to 7.820); THR est = 4.106 (95%CI 2.257 to 5.955)). The DJS had a statistically significant reduction on LoS for patients who underwent THR but not TKR. Conclusion The use of a DJS was associated with improved functional outcomes when compared to a standard 'non-digital' method. The improvements between pre-operative and post-operative outcomes in EQ-5D and OKS/OHS were higher for patients using the DJS. Furthermore, THR patients also had a shorter LoS.